Rankings analysis with the Optimized Pareto method. - Carlos Andres Delgado-Saavedra; Angel García-Baños; Victor Andrés Bucheli-Guerrero (AiBi Revista de Investigación, Administración e Ingeniería, 2020)
Rankings compare the performance of organizations. In many cases, rankings provide a good assessment of successful organizations. However, rankings often generate controversy and debate since they support the making decisions. A ranking is a weighted linear combination of indicators, and the weights assigned to each of the indicators can lead to different rank orders. In most cases, rankings are used as a tool to support making decisions, such as resource allocation; therefore, these decisions can be affected by the assignment of such weights. In this article, we analyze the behavior of a ranking and the weights; simulations are used to calculate the change in the order of the equally weighted ranking and of the randomly weighted ranking. In this regard, we present a discussion and ranking design alternatives.